2010
DOI: 10.2987/10-6004.1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hibernating Populations of Culex pipiens from a West Nile Virus Endemic Focus in New York City: Parity Rates and Isolation of West Nile Virus

Abstract: A 3-year study was undertaken to examine the parity status, survival, and prevalence of West Nile virus (WNV) in overwintering populations of Culex pipiens pipiens collected from a hibernaculum located in a WNV endemic region in New York City. Nearly 6,000 females were collected from December through April. Parity rates were highest among females collected in December and January, ranging from 12.3% to 21.9%, depending on the year. In each year of the study, the proportion of parous females declined significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 30 publications
3
31
0
1
Order By: Relevance
“…modestus playing a bridge role in specific areas [7]. Generally, in temperate regions, it has been shown that the virus may overwinter in infected female mosquitoes as well as in residential birds, so there is no need for continuous re-introductions by migrating birds [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…modestus playing a bridge role in specific areas [7]. Generally, in temperate regions, it has been shown that the virus may overwinter in infected female mosquitoes as well as in residential birds, so there is no need for continuous re-introductions by migrating birds [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WNV has been isolated from overwintering Culex adults in the Þeld (Nasci et al 2001, Bugbee and Forte 2004, Farajollahi et al 2005, Andreadis et al 2010, Unlu et al 2010. Because females destined for diapause purportedly do not blood feed (Mitchell and Briegel 1989), these Þndings suggest that vertical transmission of WNV must occur repeatedly in natural populations.…”
mentioning
confidence: 99%
“…Therefore, there was also an increased likelihood that WNV can be transmitted by hibernating mosquitoes. This hypothesis has been supported by the analysis of overwintering mosquitoes, which were infected either experimentally or naturally [146][147][148].…”
Section: Evidence Of Wnv In European Mosquitoesmentioning
confidence: 66%
“…This was demonstrated both by examining the progeny of experimentally infected mosquitoes as well as by virus isolation from male mosquitoes which must have been infected vertically because males do not take blood meals but rather feed on plant juice [130,150]. The transovarial transmission of the virus may be important for the maintenance of the infection cycle between mosquitoes and birds, as it has been shown that mosquitoes were infected with WNV during the winter diapause without having taken a blood meal [148]. The transmission rate to the gives serological evidence of an acute WNV infection.…”
Section: Evidence Of Wnv In European Mosquitoesmentioning
confidence: 99%